2010
DOI: 10.1002/cncr.25215
|View full text |Cite
|
Sign up to set email alerts
|

Data and trends in cancer screening in the United States

Abstract: BACKGROUND: This paper examines the prevalence of cancer screening use as reported in 2005 among US adults, focusing on differences among historically underserved subgroups. We also examine trends from 1992 through 2005 to determine whether differences in screening use are increasing, staying the same, or decreasing. METHODS: Data from the National Health Interview Surveys between 1992 and 2005 were analyzed to describe patterns and trends in cancer screening practices, including Papanicolaou test, mammography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
55
6

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(71 citation statements)
references
References 94 publications
(102 reference statements)
10
55
6
Order By: Relevance
“…The adherence rates in this study (overall 89.3 %) are considerably higher than in other published reports [3,6,10]. Reminder phone calls and postcards are effective in increasing rates of CRC screening [11].…”
contrasting
confidence: 67%
See 1 more Smart Citation
“…The adherence rates in this study (overall 89.3 %) are considerably higher than in other published reports [3,6,10]. Reminder phone calls and postcards are effective in increasing rates of CRC screening [11].…”
contrasting
confidence: 67%
“…Colonoscopy, regarded by most expert advisory groups as the mainstay of CRC screening, is the only modality that both detects and removes neoplastic polyps from the entire colon. Despite its efficacy, only 20-38 % of the population is adherent to CRC screening guidelines [2,3]. Colonoscopy at present is estimated to decrease CRC-related mortality by 53 %, with further decrements expected if a greater proportion of individuals received age-appropriate screening [4].…”
mentioning
confidence: 99%
“…In a population-based study, parcipitation in screening programs with fecal occult blood test was higher in patients with higher education levels, married and higher income (Frederiksen et al, 2010). Similarly (Swan et al, 2010) suggested that the rate of SC were positively associated with education and income.…”
Section: Discussionmentioning
confidence: 95%
“…This result must be tempered by knowledge that PSA testing may serve as a proxy for individual socioeconomic status. 42 In addition, more PSA screening will result in more local/regional diagnoses, leading to possible overtreatment. The risk of a local/regional diagnosis rose 2% for white males with 1 PSA test every 3 years and 6% for black males with 2 PSA tests every 3 years, versus those who had no PSA tests.…”
Section: Discussionmentioning
confidence: 99%